2006
DOI: 10.1039/b600827e
|View full text |Cite
|
Sign up to set email alerts
|

Personal exposures and indoor, residential outdoor, and urban background levels of fine particle trace elements in the general population

Abstract: The general population is exposed to particulate air pollution from many different local and regional sources. Examples of local sources are traffic, biomass burning and resuspended dust, while regional sources are dominated by combustion processes from heating, traffic and industries. The overall aim of this thesis was to characterise the personal exposure to trace elements in fine particles, mainly PM 2.5 and investigate how the exposure is related to indoor and outdoor levels. Particulate matter was collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 79 publications
2
44
0
1
Order By: Relevance
“…In an extension of the present study, the particle mass was analyzed for trace elements. Differences between air masses regarding elemental composition were large enough to be significant even for personal exposure to and indoor levels of elements of outdoor origin, such as sulfur, vanadium, lead, and chlorine (Molna´r et al, 2006). In our study, five out of 42 measurements of urban background levels of PM 2.5 were above 25 mg/m 3 , the recommended air quality guideline from WHO (99th percentile, 3 days/year).…”
Section: Influence Of Long-range Transportmentioning
confidence: 46%
“…In an extension of the present study, the particle mass was analyzed for trace elements. Differences between air masses regarding elemental composition were large enough to be significant even for personal exposure to and indoor levels of elements of outdoor origin, such as sulfur, vanadium, lead, and chlorine (Molna´r et al, 2006). In our study, five out of 42 measurements of urban background levels of PM 2.5 were above 25 mg/m 3 , the recommended air quality guideline from WHO (99th percentile, 3 days/year).…”
Section: Influence Of Long-range Transportmentioning
confidence: 46%
“…The data on the elemental concentrations can be found in Molnár et al (2006). The chemically undetermined part of PM 2.5 , PM rest , accounted for, on average, 59% of the total PM 2.5 .…”
Section: Resultsmentioning
confidence: 99%
“…was provided by the Environmental Agency in Gothenburg. More detailed information regarding the study design, the participants, and the sampling can be found in Molnár et al (2006) and Johannesson et al (2007). The study was approved by the Ethics Committee at the University of Gothenburg.…”
Section: Study Design Participants and Sampling Equipmentmentioning
confidence: 99%
See 2 more Smart Citations